Growth expectations, undue optimism, and short-run fluctuations - Enders, Zeno; Kleemann, Michael; Müller, Gernot J. (CESifo working papers, 2013)
We assess the contribution of "undue optimism" (Pigou) to short-run fluctuations. In our analysis, optimism pertains to total factor productivity which determines economic activity in the long run, but is not contemporaneously observed by market participants. In order to recover optimism shocks - autonomous, but fundamentally unwarranted changes in the assessment of productivity - from actual time series, we rely on an informational advantage over market participants. Specifically, we compute the nowcast error regarding current output growth drawing on the Survey of Professional Forecasters. Including nowcast errors in a vector autoregression model makes it possible to identify optimism shocks. Optimism shocks, in line with theory, induce a negative nowcast error but raise economic activity in the short run. They account for up to 30 percent of short-run fluctuations.